Comparing the effects of trunk stabilisation and activation exercises on pain and disability in postpartum lumbo-pelvic pain (randomised controlled trial) - Chaudhry, Rabia Yousaf; Muneeb, Hafiza Neelam; Ameena Amjad; Shafique, Sidra; Naseem, Aqsa; Shahzadi, Nafisa (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to determine and compare the effects of trunk stabilisation and activation exercises on pain and disability in postpartum lumbo-pelvic pain. It was a randomised clinical trial (ClinicalTrials.gov: NCT05490810). Twenty-eight females with lumbo-pelvic pain were randomly allocated to two groups with 14 patients in each group. Group A was treated with trunk stabilisation exercises and Group B was treated with trunk activation exercises, three times a week for eight weeks. Numeric pain rating scale was used to measure the intensity of pain. Disability was assessed through Oswestry disability index (ODI). Both the groups were evaluated before and at the end of the last treatment session. Data was analysed by SPSS 21. There was a significant difference between trunk stabilisation versus activation exercises on pain and disability in postpartum lumbo-pelvic pain with p value <0.05 in Group A patients. —Continue